Conservation and viability of dragon fruit (Hylocereus polyrhizus Weber) pollen grains - Fagundes, Miriã Cristina Pereira (2017)
The dragon fruit is an exotic and promising fruit in Brazil, mainly due to its organoleptic characteristics. The fruits beyond the pleasant taste are rich in vitamins, minerals, essential fatty acids, among other benefits and advantages. However, despite its expansion, t here are only a few researches about dragon fruit in Brazil. In addition to studies on management, it is necessary to study the reproductive biology, especially about the viability and conservation of pollen grains, an important tool in breeding programs. The objective of this research was to establish a suitable culture medium for in vitro germination and to evaluate the germinative power of red pulp dragon fruit pollen grains after storage at low temperatures. In the first experiment for the determination of the medium were installed four experiments sequentially: I) Agar (6, 8 and 10 g L-1) and pH (5, 6 and 7); II) Sucrose (0, 25, 50, 75, 100 and 125 g L -1 ); III) Calcium nitrate (0, 200, 400, 600, 800 and 1000 mg L -1 ); IV) Boric acid (0, 200, 400, 600, 800 and 1000 mg L -1 ), all in a completely randomized design with four replications. Pollen tube length and percentage of germination of pollen grains were evaluated. It is concluded that the medium for the germination of dragon fruit pollen grains should be increased by 100 g L -1 sucrose, 518 mg L -1 calcium nitrate and 636 mg L -1 boric acid, the pH being measured to 5 and the medium solidified with 6 g L -1 agar. The concentration of 500 mg L -1 of boric acid gives higher pollen tube lengths. In the second experiment the pollen grains were kept under the following storage conditions: T1, refrigerator (4 °C); T2, freezer (-20 °C) and T3, ultrafreezer (-80 °C), over a period of eight weeks. The evaluation of the viability of the pollen was performed (7, 15, 30, 45 and 60 days) by in vitro germination test. The experimental design was completely randomized, in a factorial arrangement 3 x 5 (3 temperatures x 5 time) with four replications. Storage conditions under refrigerator (4 °C) and freezer (-20 °C) are recommended for short-term storage and the ultra-freezer (-80 °C) has promoted better longterm pollen viability.